The State of Identification Systems in Africa : Country Briefs - World Bank Group (World Bank, Washington, DC, 2017)
The global landscape of identification (ID) is changing rapidly. Technology is making it cheaper to identify people accurately, while the opportunities of the digital era are making it more important to be able to prove one’s identity. The role of ID systems has become essential in areas ranging from financial inclusion, social protection, migration, and even coping with natural disasters. Based on the World Bank’s identification for development (ID4D) program’s database, more than 40 percent of those lacking IDs in the world live in Africa. For the first time, the World Bank is planning to provide financial support and technical assistance to ID systems in Africa; this is an area in which it has had marginal involvement until now. The knowledge base related to ID systems in Africa has expanded dramatically. Applying a standardized assessment approach, the World Bank has financed more than 20 country reports and produced a synthesis report covering 17 of them. This publication draws from those reports as well as primary and secondary sources to provide a brief sketch of the foundational ID system in 48 African countries. The brief also confirms that the gaps in the legal and institutional environment that were found in the subset of countries covered in the synthesis report are representative of the wider African context. This volume represents a very small step toward increasing the understanding of the rapidly changing landscape of ID systems in Africa.